Double-Sided Metasurface Array for a Dual-Band and Polarization-Independent Microwave-Energy-Harvesting System - Maged A. Aldhaeebi (MDPI AG, 2021)
In this article, we present a simple and novel design of a double-sided metasurface for a dual-band and polarization-independent microwave-energy-harvesting system. The proposed metasurface is constructed from the dual-sided design of 8 × 8 unit cells. Different from the regular dual-band unit cells that contain two loops or multiple shapes of resonators printed in the same layer, the proposed metasurface is based on designing double loops, each combined with two arms of a dipole printed on the top and bottom sides of a single substrate. Thus, the bottom layer is utilized to generate the second frequency band of interest. Three main numerical simulations were conducted to investigate the performance of a single unit cell, a 2 × 2 supercell, and an array of an 8 × 8 metasurface structure. The numerical simulation demonstrated that 98% and 95% of the incident energy is collected at two bands of 1.8 and 6.5 GHz for the proposed harvester.